A quantitative shotgun proteomics analysis of germinated rice embryos and coleoptiles under low-temperature conditions. Issue 1 (December 2015) - Lee, Joohyun; Lee, Wondo; Kwon, Soon-Wook
Abstract Background At low temperatures, rice grains have a reduced germination rate and grow more slowly, which delays the emergence of rice seedlings from the paddy water surface and significantly increases seedling mortality. In this study, we conducted a shotgun proteomics analysis of geminated embryos and coleoptiles to compare the proteome expression pattern between the low-temperature resistant variety, Tong 88-7, and the low-temperature susceptible variety, Milyang 23. Results In a shotgun proteomics analysis of low-temperature resistant and susceptible embryos and coleoptiles in both cold and control temperatures, we discovered a total of 2626 non-redundant proteins, with a 0.01 false discovery rate. A comparison of protein expression patterns between resistant and susceptible embryos and coleoptiles under low-temperature and normal conditions revealed that 85 proteins and 196 proteins were expressed by the resistant and susceptible strains, respectively, in response to low temperature. Among them, 12 proteins overlapped. Proteins involved in stress responses, metabolism, and gene expression were expressed in both strains. Conclusions Similar molecular functions of the response were detected, suggesting that the resistant and susceptible strain have a similar proteome response to cold temperatures. The resistance of Tong 88-7 to cold-water germination may result from the efficiency of these proteins, rather than activation of additional or different molecular processes. A comparison of protein expression between the resistant and susceptible strains' responses revealed that the more successful low-temperature germination of Tong 88-7 was associated with gibberellin signaling, protein trafficking, and the ABA-mediated stress response.